Multiproduct quality competition: fighting brands and product line pruning - Myatt, D; Johnson, J (University of Oxford, 2002)
Firms selling multiple quality-differentiated products frequently alter their product lines when a competitor enters the market. We present a model of multiproduct monopoly and duopoly using a general 'upgrades' approach that yields a powerful analytical framework. We provide a simple theoretical explanation for the common strategies of using 'fighting brands' and of product line 'pruning'. We also present a general condition that guarantees that a monopolist will forsake market segmentation opportunities and sell but a single product. A number of previously studied issues can be addressed by our model, including inter-temporal price discrimiation and 'damaged goods'.